Effect of tomato (Solanum lycopersicum L.) protein on carcass and meat quality of kampong chicken - Leke, J. R.; Mandey, J. S.; Ratulangi, F.; Najoan, M. (Diponegoro University, 2018)
The purpose of this research was to examine the carcass quality and meat quality of native chicken fed dried tomato meal in diet. The study was conducted by using 200 heads of native chickens 10 days. The birds were divided into five experimental diets and each was divided into four replicate groups of ten birds per replicate. The based diet was formulated to contain 42% corn, rice bran 9%, fish meal 10%, fish oil 5%, soybean meal 9% and commercial diets 25%. Tomato meal was included in five experimental diets at levels of 0, 3, 6, 9, 12% to substitute based diets. The treatments were PO = 100% based diet (BD) + 0% tomato meal (TM); P1 = 97% BD+ 3% TM; P2 = 94% BD + 6% TM;P3 = 91% BD + 9% TM; P4 = 88% BD + 12% TM. Chemical composition of tomato meal was: 20.73% crude protein, 1.53% fat, 30.94%crude fiber, 0.98% Ca, 1.20% P and 2,416 kcal/kg of Gross Energy (GE). Results showedthat feeding tomato meal at an inclusion rate of 12% increased slaughter weight, carcass, breast meat, wings, drumstick and thigh, and decreased abdominal fat and blood cholesterol. Moreover, there were no significant difference in giblet (liver, heart and gizzard) between treatments. Meat water and meat crude protein were significantly increased. Meat crude fat and meat cholesterol were significantly decreased. In conclusion, tomato meal can be used as an alternative feedstuff in kampong chicken diets at inclusion levels up to 12% without negative effects on carcass quality and meat quality.